144 Interstitial Laser Anterior Capsulotomy for Obsessive-compulsive Disorder: Lesion Size and Tractography Correlate with Outcome. (1st April 2022) - Satzer, David I.; Mahavadi, Anil; Lacy, Maureen; Grant, Jon; Warnke, Peter C.
Abstract : INTRODUCTION: Anterior capsulotomy is a well-established treatment for refractory obsessive-compulsive disorder (OCD) and has been performed with radiofrequency ablation, stereotactic radiosurgery, and focused ultrasound. MRI-guided laser interstitial thermal therapy (LITT) allows creation of larger, more demarcated lesions with the safety conferred by real-time imaging of the ablation volume. METHODS: Patients with severe OCD refractory to pharmacotherapy and cognitive-behavioral therapy underwent bilateral anterior capsulotomy via LITT. The primary outcome was percent reduction in Yale-Brown Obsessive Compulsive Scale (Y-BOCS) score over time. Lesion size was measured on post-ablation MRI. Disconnection of the anterior limb of the internal capsule (ALIC) was assessed via individual and normative tractography. RESULTS: Eighteen patients underwent laser anterior capsulotomy. Median follow-up was 6 months (range 3-51 months). Time occupied by obsessions improved immediately (median Y-BOCS item 1 score 4 to 1, P = 0.0002). Mean (± standard deviation) decrease in Y-BOCS score at last follow-up was 46 ± 32% (16 ± 11 points; P = 0.0002). Sixty-one percent of patients were responders. One patient had an asymptomatic intracerebral hemorrhage. Reduction in Y-BOCS score was positively associated with ablation volume (P = 0.006). Individual tractography demonstrated durable ALIC disconnection. Normative tractography revealed a dorsal-ventral gradient, with disconnection of orbitofrontal streamlines most strongly associated with a positive response to surgery (P < 0.0001). CONCLUSION: Laser anterior capsulotomy resulted in immediate, marked improvement in OCD symptom severity. Larger lesions can be created safely and permit greater disconnection of the prefrontal-subcortical pathways involved in OCD. The importance of greater disconnection is presumably related to variation in ALIC structure and the complex role of the PFC in OCD.